Hugo at the Window - Rockwell, Anne (Hodder and Stoughhton Ltd, 1991)
Hugo the dog waits and waits at the window for his friend who is gone a long time, but there is a surprise for Hugo when his friend returns.
Keywords: Juvenile literature-Dogs-Fiction